Evaluation of Extraradicular Diffusion of Hydrogen Peroxide during Intracoronal Bleaching Using Different Bleaching Agents - Mohammad E. Rokaya; Khaled Beshr; Abeer Hashem Mahram; Samah Samir Pedir; Kusai Baroudi (International Journal of Dentistry)
Objectives. Extra radicular diffusion of hydrogen peroxide associated with intracoronal teeth bleaching was evaluated. Methods. 108 intact single rooted extracted mandibular first premolars teeth were selected. The teeth were instrumented with WaveOne system and obturated with gutta percha and divided into four groups (n=27) according to the bleaching materials used. Each main group was divided into three subgroups (n=9) according to the time of extra radicular hydrogen peroxide diffusion measurements at 1, 7, and 14 days: group 1 (35% hydrogen peroxide), group 2 (35% carbamide peroxide), group 3 (sodium perborate-30% hydrogen peroxide mixture), and group 4 (sodium perborate-water mixture). Four cemental dentinal defects were prepared just below the CEJ on each root surface. The amount of hydrogen peroxide that leached out was evaluated after 1, 7, and 14 days by spectrophotometer analysis. The results were analyzed using the ANOVA and Tukey’s test. Results. Group 1 showed highest extra radicular diffusion, followed by group 3 and group 2, while group 4 showed the lowest mean extra radicular diffusion. Conclusion. Carbamide peroxide and sodium perborate-water mixture are the most suitable bleaching materials used for internal bleaching due to their low extra radicular diffusion of hydrogen peroxide.